Development of a short-term assay based on the evaluation of the plasma membrane integrity of the alga Pseudokirchneriella subcapitata - Machado, Manuela D. (2017)
Membrane integrity has been used as a criterion for the definition of cell viability. In the present work, staining conditions (time and dye concentration) for the evaluation of membrane integrity in a fluorescence microplate reader, using the membrane-impermeant nucleic-acid dye SYTOX Green, were optimized. Incubating Pseudokirchneriella subcapitata algal cells with 0.5 μmol/l SYTOX Green for 40 min allowed a clear discrimination between live (intact plasma membrane) and dead cells (with compromised plasma membrane). Algal cell suspensions, labelled with SYTOX Green, exhibited a green fluorescence proportional to the fraction of the cells with a permeabilized plasma membrane. The optimized staining conditions were used to assess the toxicity of 1-pentanol on P. subcapitata in a short-term exposure (6 h) assay. The loss of membrane integrity in the cell population increased with the concentration of 1-pentanol. The 6-h EC10 and EC50 values were 7,617 mg/l 1-pentanol (95 % confidence limits 4,670–9,327) and 12,818 mg/l 1-pentanol (95 % confidence limits 10,929–15,183), respectively. The developed microplate-based short-term assay can be useful in the highthroughput screening of toxics or environmental samples using the alga P. subcapitata.